India's undernourished children a call for reform and action - Gragnolati Michele; Bredenkamp Caryn; Das Gupta Monica; Lee Yi-Kyoung; Shekar Meera (Washington World Bank, 2006)
Drawing on qualitative studies and quantitative evidence from large household surveys, this book explores the dimensions of child undernutrition in India and examines the effectiveness of the Integrated Child Development Services (ICDS) program in addres
Keywords: Health and hygiene; India; Integrated Child Development Services (India); Malnutrition in children; Poor children